The Predictability of English Reading Skill from Indonesian Reading Skill and English Knowledge at Students of SMAN 1 Pademawu-Pamekasan - Haqiqiyah , Muflihatul (Al-Insyiroh: Jurnal Studi Keislaman, 2020)
The basic problem wants to discuss is: Do Indonesian reading skill and English knowledge correlate with English reading skill at students of SMAN 1 Pademawu ? The purpose of the research is find the correlation between Indonesian reading skill and English knowledge on English reading skill at students of SMAN 1 Pademawu. The research gave some useful information about students’ Indonesian reading skill and English knowledge on English reading skill. This research also presented the description and the correlation between students’ Indonesian reading skill and English knowledge on English reading skill. The technique of collecting data was by using a test. After the data of the students’ Indonesian reading tests and English knowledge tests and English reading tests collected, the data was statistically computed (SPSS 17.00) to find out the correlation between the two variables. From the tests, it was found out there was not a significant correlation with students’ Indonesian reading skill and English knowledge on English reading skill. It is suggested that to have a good capability in English reading skill, students should have a good ability in Indonesian reading skill and English knowledge.